School Responsibility and Improvement Pathways in the Prevention and Control of Campus Bullying in China: An Analysis of 155 Civil Judgments - Xuanyu Chen; Yulu Jin; Feng Han (Social Sciences)
Schools play a central role in the prevention and control of school bullying, and there are both theoretical and practical grounds for legally establishing their obligations in this regard. This study employs a mixed-methods approach, primarily qualitative research supplemented by quantitative analysis, to conduct textual analysis and coding of 155 civil judgments on school bullying litigation in China. It aims to explore the main scenarios where schools are held liable for failing to fulfill their prevention and intervention obligations, and to examine the impact of school accountability on bullied students. Through textual analysis and t-tests, this study found that schools are primarily held liable for inadequate prevention, failure to detect or allowing bullying behavior, and failure to provide timely assistance to victims. Meanwhile, neglecting antibullying obligations exacerbates the mental harm suffered by victims. However, as public educational institutions, schools should not bear an excessive legislative burden, as this could increase their workload and lead to resistance in practice. Therefore, it is crucial to strike a balance and refine school responsibilities. Establishing clear legal obligations for schools can help clarify the standards for school liability in judicial decisions. Accordingly, improving fundamental antibullying obligations, granting schools a certain degree of disciplinary discretion, and enhancing guidance in high-risk situations can ensure the fulfillment of essential responsibilities while empowering schools to effectively combat bullying.